1999
DOI: 10.1002/(sici)1097-0185(19990101)254:1<107::aid-ar14>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Microvasculature of crotaline snake pit organs: Possible function as a heat exchange mechanism

Abstract: The infrared sensory membranes of the pit organs of pit vipers have an extremely rich capillary vasculature, which has been noted passim in the literature, but never illustrated or studied in detail. We rendered the pit vasculature visible in various ways, namely, by microinjection of India ink, by a combination of ink and succinate dehydroge-nase staining, and by making resin casts for scanning electron microscope study. We also used transmission electron microscopy for identifying the types (arterioles, venu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…10° in the forward direction (see also DeSalvo and Hartline, 1978). The importance of forward imaging is indicated by a higher density of receptors and associated blood vessels on the portion of the membrane corresponding to objects directly in front of the head (Amemiya et al, 1999;Goris and Nomoto, 1967;Goris and Terishima, 1973). Viewed from the forward direction, the external aperture is higher than it is wide (Fig.·1A) and the optical spread function is therefore subelliptical.…”
Section: Methodsmentioning
confidence: 99%
“…10° in the forward direction (see also DeSalvo and Hartline, 1978). The importance of forward imaging is indicated by a higher density of receptors and associated blood vessels on the portion of the membrane corresponding to objects directly in front of the head (Amemiya et al, 1999;Goris and Nomoto, 1967;Goris and Terishima, 1973). Viewed from the forward direction, the external aperture is higher than it is wide (Fig.·1A) and the optical spread function is therefore subelliptical.…”
Section: Methodsmentioning
confidence: 99%
“…In Crotalus the receptors in the facial pit's sensory membrane contribute to three branches of the trigeminal nerve (Fig.3); our anatomical results suggest that C. atrox is similar to other pit vipers in both the position and minimal overlap of the three respective fields on the sensory membrane (Bullock and Fox, 1957;Amemiya et al, 1999). This study recorded from only one (the superficial maxillary) of these three branches.…”
Section: Discussionmentioning
confidence: 49%
“…Though we cannot provide a definitive explanation for this discrepancy, we hypothesize that it is due to heterogeneous distribution of receptor organs in the posterior portion of the sensory membrane. The spread functions were created assuming a homogeneous spatial distribution of receptors; previous workers have suggested that there is an area of increased receptor density in the posterior portion of the membrane (Amemiya et al, 1999). A localized cluster of increased receptor density could function like a thermal fovea; in any case it would increase local sensitivity that could skew the experimental results relative to the biophysical predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Although an entire class of infrared imaging cameras employs cryogenic elements, de Cock Buning (1984) has argued that cooling of the pit organs would not increase their thermal resolution. However, a complex network of capillaries on the pit membrane is at least suggestive of a heat exchanger, in which case temporal resolution of the pit organ may depend on the periodic influx of cooled blood to ''erase'' thermal afterimages (Amemiya et al, 1999). A second possible function of cool pits relates to their operational temperature range.…”
Section: Discussionmentioning
confidence: 99%